Global biogeographic patterns of the genus Indigofera (Fabaceae: Indigofereae) - Du Preez, Brian; Schrire, Brian D.; Dreyer, Léanne L.; Stirton, Charles H.; Chimphango, Samson B. M.; Muasya, A. Muthama (Revista brasileira de botânica, 2025)
Indigofera L. is the most diverse genus in the tribe Indigofereae and the third largest genus in the Fabaceae with over 750 species distributed in most tropical to temperate areas of the world. The centre of diversity of the genus lies on the African continent, accounting for over two-thirds of its global diversity. Diversification of Indigofer a’s four main clades began in the Early Miocene, with the Tethyan and Cape Clades having slightly older crown ages than the Pantropical and Paleotropical Clades. Using biogeographical models under a newly assembled, more comprehensively-sampled ITS phylogeny, we confirmed that the tribe Indigofereae originated in the Africa-Madagascar centre, with the genus Indigofera resolving with a mainland African origin c. 38 Mya. Long-distance dispersals were rare, but did occur from Africa to South America and Africa to Australia during the late Miocene. Multiple dispersals from Africa into Asia took place via the arid north-east African and Arabian corridors during the same period. At least four Indigofera dispersals to Madagascar took place during the Miocene. The Cape Clade is a narrowly endemic lineage, mostly restricted to the Greater Cape Floristic Region (GCFR) of southwestern South Africa, while the Tethyan, Pantropical and Paleotropical Clades are more widely dispersed across multiple continents. Both the Cape and Tethyan Clades display strong signals for arid origins in the southern Namib and Richtersveld regions of Southwestern Africa. This study emphasizes the importance of the global Succulent biome in shaping biogeographical patterns of Indigofera globally, particularly in terms of biome conservatism and how it created corridors facilitating trans-continental dispersal.